Optimization of the Well Production Mode Based on Retro-analysis of the Power Features of Subsea Fluid Pipelines - Ismayilov, G.G.; Ismayilov, Sh.Z.; Ismayilov, Sh.Z.; Sultanova, A.V. (Herald of Azerbaijan Engineering Academy, 2024)
An experience in the operation of subsea pipelines, which are part of the existing offshore collection system, shows that for trouble-free and efficient operation of the collector-transport system and its individual subsea pipelines, it is important to choose the optimal operating modes. In the article, based on known calculation methods and considering the characteristics of heterogeneous well products, an analytical method for hydraulic calculation and determination of the optimal operating mode of liquid pipelines is developed, which is tested at the Gunashli field.